Marinated fish - Mumbai Archive Project Team (Jio Institute, 2024)
In certain recipes, the fish must be coated with a mixture of rice flour and semolina (suji) before frying it to give it a crispy texture. Although optional, this step improves the dish's flavour and texture. Pomfret is cooked in a tandoor after it is marinated in traditional spices and yogurt (dahi).